The complete mitochondrial genome and phylogenetic implications of Paradoxopsyllus custodis and Stenischia montanis yunlongensis - Bin Chen; Mingna Duan; Shuang Liu; Yafang Liu; Shaobo Tang; Dandan Jiang; Wei Gu; Quanfu Zhang; Xing Yang (Scientific Reports)
Abstract Fleas, which are ubiquitous small wingless parasitic insects, have a significant impact on human and animal health globally. In this study, we sequenced and analyzed the complete mitochondrial genomes of Paradoxopsyllus custodis and Stenischia montanis yunlongensis. The lengths of these genomes were 15,375 bp and 15,651 bp respectively, encompassing a total of 37 genes. Notably, all nucleotide combinations displayed a marked AT preference, with ATN as start codon for all 13 protein-coding genes in both species. Furthermore, only two genes in Paradoxopsyllus custodis were terminated with an incomplete stop codon T(AA). The five most frequently utilized codons among the 13 PCGs in both species ended with A / U, and their relative synonymous codon usage values surpassed 2. Phylogenetic relationships among fleas were assessed using maximum likelihood (ML) and Bayesian inference (BI), providing support for the paraphyletic of Leptopsyllidae. This study not only enhances our understanding of the mitochondrial genome within the genera Paradoxopsyllus and Stenischia, but also offers valuable genetic markers for the taxonomic identification and phylogenetic evolution within the order Siphonaptera.